2016
DOI: 10.4269/ajtmh.16-0053
|View full text |Cite
|
Sign up to set email alerts
|

West Africa International Centers of Excellence for Malaria Research: Drug Resistance Patterns to Artemether–Lumefantrine in Senegal, Mali, and The Gambia

Abstract: Abstract. In 2006, artemether-lumefantrine (AL) became the first-line treatment of uncomplicated malaria in Senegal, Mali, and the Gambia. To monitor its efficacy, between August 2011 and November 2014, children with uncomplicated Plasmodium falciparum malaria were treated with AL and followed up for 42 days. A total of 463 subjects were enrolled in three sites (246 in Senegal, 97 in Mali, and 120 in Gambia). No early treatment failure was observed and malaria infection cleared in all patients by day 3. Polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 44 publications
3
18
1
Order By: Relevance
“…It seems that other resistance mechanisms and therefore other molecular markers may exist in Africa compared to those in Asia. This phenomenon has also been observed with resistance to artemisinin, which is associated with pfk13 polymorphisms in Asia, while no polymorphism is observed in most cases of clinical failure of ACT in Africa (10,(31)(32)(33)(34)(35). To overcome the limitation of this study, i.e., the low number of samples with reduced susceptibility, it is imperative to further assess more isolates from different geographical areas of Africa, and especially more P. falciparum strains resistant to PPQ from Africa.…”
mentioning
confidence: 75%
“…It seems that other resistance mechanisms and therefore other molecular markers may exist in Africa compared to those in Asia. This phenomenon has also been observed with resistance to artemisinin, which is associated with pfk13 polymorphisms in Asia, while no polymorphism is observed in most cases of clinical failure of ACT in Africa (10,(31)(32)(33)(34)(35). To overcome the limitation of this study, i.e., the low number of samples with reduced susceptibility, it is imperative to further assess more isolates from different geographical areas of Africa, and especially more P. falciparum strains resistant to PPQ from Africa.…”
mentioning
confidence: 75%
“…A handful of studies over the past decade have investigated the e cacy of AL in Mali, and reported PCRcorrected e cacies greater than 98%. These include: a 2010-2014 study in Sotuba, Kolle, and Banambani [20]; a 2012-2014 study in Dioro [21]; and a 2013-2015 study in Doneguebougou and Torodo [22]. Although two of these studies [20,22] considered reinfections as treatment successes in their calculation of PCR-corrected e cacy (an approach not consistent with WHO guidelines), the e cacy results remained above 97% when recalculating e cacy using the WHO-endorsed approach of eliminating reinfections from the calculation.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016 none of the previously described substitutions had been observed generally in sub-Saharan Africa apart from the P553L mutation which was observed at low frequencies in Kenya (0.53%) and in Malawi (0.59%) [37] [38]. Other studies have however observed the presence of synonymous or non-K13 mutations correlated with a delay in parasite clearance in Burkina Faso (2.26%), Senegal (5.5%) and Togo (1.8%) [8] [39] [40] (Table 4).…”
Section: K13 Mutants In West Africamentioning
confidence: 96%
“…Most of the mutations reported in the reviewed publications relate to delayed parasite clearance but are not confirmed to be resistant to artemisinin. Artemisinin, its derivatives and artemisinin-based combinations (ACT) still remain effective as the first line of treatment for malaria in West Africa[28] [38].…”
mentioning
confidence: 99%